Dietary compliance in Iranian children and adolescents with celiac disease - Taghdir M; Honar N; Mazloomi SM; Sepandi M; Ashourpour M; Salehi M (Journal of Multidisciplinary Healthcare, 2016)
Maryam Taghdir,1 Naser Honar,2 Seyed Mohammad Mazloomi,3 Mojtaba Sepandi,4 Mahkameh Ashourpour,1 Musa Salehi5 1Student Research Committee, Department of Clinical Nutrition, School of Nutrition and Food Sciences, Shiraz University of Medical Sciences, Shiraz, Iran; 2Department of Pediatric Gastroenterology and Hepatology, Shiraz University of Medical Sciences, Shiraz, Iran; 3Nutrition Research Center, Department of Food Hygiene and Quality Control, School of Nutrition and Food Sciences, Shiraz University of Medical Sciences, Shiraz, Iran; 4Department of Epidemiology and Biostatistics, Baqyiatallah University of Medical Sciences, Tehran, Iran; 5Nutrition Research Center, Department of Clinical Nutrition, School of Nutrition and Food Sciences, Shiraz University of Medical Sciences, Shiraz, Iran Introduction: Celiac disease (CD) is caused due to intake of gluten, a protein component in wheat, barley, and rye. The only treatment currently available for CD is strict lifetime adherence to a gluten-free diet (GFD) which is a diet that excludes wheat, barley, and rye. There is limited information on barriers to following a GFD. The present study aimed to investigate the compliance with a GFD, barriers to compliance, and the impact of compliance on the quality of life (QOL) in Iranian children and adolescents suffering from CD.Methods: In this cross-sectional study, a total of 65 known cases of CD (both males and females), diagnosed in Namazi Hospital, a large referral center in south of Iran, selected by census were studied in 2014. Dietary compliance was assessed using a questionnaire. A disease-specific QOL questionnaire for children with CD (the celiac disease DUX [CDDUX]) was used. Comparisons between categorical variables were performed using chi-square test.Results: Sixty-five patients, 38 females (58.5%) and 27 (41.5%) males, were surveyed. Mean (± standard deviation [SD]) age of the respondents was 11.3 (±3.8) years. Dietary compliance was reported by 35 (53.8%) patients. The mean (± SD) CDDUX score was higher in dietary-compliant patients (33.5 [±19.4] vs 26.7 [±13.6], respectively, P=0.23). The score of CDDUX in parents of patients in dietary-compliant group was more than the noncompliant patients (28.1 [±13.5] vs 22.1 [±14], respectively, P=0.1). Barriers to noncompliance were poor or unavailability (100%), high cost (96.9%), insufficient labeling (84.6%), poor palatability (76.9%), and no information (69.23%).Conclusion: Approximately half of the patients with CD reported dietary compliance. Poor or unavailability was found to be the most important barrier contributing to noncompliance. The QOL was better in compliant patients. Proposed strategies to improve compliance are greater availability of gluten-free products, better food labeling, and better education about the diet and condition. Keywords: child, gluten enteropathy, adherence, gluten-free diet, quality of life